Utility Of The Alvarado Score In The Diagnosis And Management Of Right-Lower-Quadrant Abdominal Pain: A Prospective Observational Study - Desai, Rahulkumar; Patel, Aayush; Jha, Siddharth; Shah, Abhigna; khandra, Hitesh (Journal of Neonatal Surgery, 2025)
Background: Right-lower-quadrant (RLQ) abdominal pain is a frequent presentation in emergency departments, where timely differentiation of acute appendicitis from other mimickers is crucial. The Alvarado score (AS) is a bedside clinical tool developed to standardise diagnosis, yet its real-world diagnostic performance in contemporary Indian practice remains under-reported. Methods: We prospectively enrolled 100 consecutive patients (10–50 years; February–November 2023) presenting with RLQ pain to GMERS Medical College & General Hospital, Gandhinagar. After informed consent, each patient underwent detailed history, examination, complete blood count and ultrasound (USG). AS (0–10) was calculated and categorised as 1-4, 5-6 or ≥ 7. Surgical decision-making incorporated AS, USG and consultant judgement. Operated specimens underwent histopathological examination (HPE). Sensitivity, specificity and positive-predictive value (PPV) of AS ≥ 7 for histologically proven appendicitis were computed. Results: Male-to-female ratio was 1.27 : 1 (56/44). AS distribution was 1-4 (20 %), 5-6 (28 %) and ≥ 7 (52 %). USG suggested appendicitis in 78 % overall, rising from 45 % in AS 1-4 to 92 % in AS ≥ 7. Seventy patients underwent appendicectomy (48 with AS ≥ 7); 94 % were laparoscopic. Histology confirmed inflamed appendix in 66/70 (94 %). For AS ≥ 7, sensitivity was 71.2 %, specificity 75 % and PPV 97.9 % for histologically proven appendicitis. No missed perforations or negative laparotomies occurred in the conservative cohort. Conclusion: An Alvarado score ≥ 7 provides excellent PPV and acceptable sensitivity for diagnosing appendicitis and safely guides operative management, whereas scores ≤ 6 warrant adjunct imaging and observation. Incorporating AS into standard care may reduce negative appendicectomy rates and optimise resource utilisation in busy Indian emergency settings